2020
DOI: 10.1007/s00259-020-05160-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of dual tracer PET/CT: PSMA ligand and [18F]FDG PET/CT in patients undergoing [177Lu]PSMA radioligand therapy

Abstract: Background Prostate-specific membrane antigen (PSMA)-targeted radioligand therapy (RLT) with 177Lu-labeled PSMA ligands has achieved remarkable results in advanced disease stages of metastatic castration-resistant prostate cancer (mCRPC). However, not all patients benefit from this therapy. Different treatment responses could be explained by tumor heterogeneity triggered by progression and the number of prior treatments. PSMA-negative lesions can be missed on PSMA ligand PET/CT, which subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 25 publications
3
88
0
Order By: Relevance
“…Therefore, weighting between SUV and TV, future studies may also investigate such sophisticated volumetric quantification approaches for outcome prediction [15]. A dual-radiotracer approach using PSMA-PET and 2-deoxy-2-[F-18]fluoro-D-glucose has also been performed [2,29], and intertumoral heterogeneity in PC assessed by both radiotracers may be of clinical significance for OS in a manner similar to established dual-tracer imaging protocols for neuroendocrine tumors [30,31]. Therefore, future studies may also consider findings on PSMA-PET with simultaneous increased glucose consumption, and thus, the predictive potential of FDG(+)/PSMA(-) lesions for early biochemical response could also be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, weighting between SUV and TV, future studies may also investigate such sophisticated volumetric quantification approaches for outcome prediction [15]. A dual-radiotracer approach using PSMA-PET and 2-deoxy-2-[F-18]fluoro-D-glucose has also been performed [2,29], and intertumoral heterogeneity in PC assessed by both radiotracers may be of clinical significance for OS in a manner similar to established dual-tracer imaging protocols for neuroendocrine tumors [30,31]. Therefore, future studies may also consider findings on PSMA-PET with simultaneous increased glucose consumption, and thus, the predictive potential of FDG(+)/PSMA(-) lesions for early biochemical response could also be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Of the study group, 18 of 54 (33%) patients had FDG+/PSMAlesions at PET/CT scan. They showed that FDG positive and PSMA negative uptake was a negative predictor for overall survival (6.0 ± 0.5 months vs. 16 ± 2.4 months) [58].…”
Section: Predictors Of Efficacymentioning
confidence: 99%
“…Hence, addition of FDG PET/CT to identify discordant disease appears to assist in optimal selection of patients most likely to benefit from PSMA-TRT. In another study, retrospective comparison of patients with at least one FDG-positive, but PSMA-negative (FDG+/PSMA-) lesion to patients without any FDG+/PSMA- lesions revealed a significant lower OS in the latter group, providing corroborating evidence that FDG+/PSMA- lesions are a negative predictor of OS in patients with mCRPC undergoing RLT [ 20 ].…”
Section: Imaging Biomarkersmentioning
confidence: 83%